Drag Reduction Using Passive Methods on KIA PRIDE Car Model - Zahraa Mahdi Saleh; Anmar Hamid Ali; Mustafa Sabeeh Abood (Journal of Engineering, 2020)
An experimental study on a KIA pride (SAIPA 131) car model with scale of 1:14 in the wind tunnel was made beside the real car tests. Some of the modifications to passive flow control which are (vortex generator, spoiler and slice diffuser) were added to the car to reduce the drag force which its undesirable characteristic that increase fuel consumption and exhaust toxic gases. Two types of calculations were used to determine the drag force acting on the car body. Firstly, is by the integrating the values of pressure recorded along the pressure taps (for the wind tunnel and the real car testing), secondly, is by using one component balance device (wind tunnel testing) to measure the force. The results show that, the average drag estimated on the baseline car for different Reynolds numbers was (0.381) and the drag force was reduced by adding a spoiler and a slice diffuser to (4.45%, 1.5%) respectively, whereas the amount of drag reduction was (5.46%) when all drag reduction modifications were added together on the base car. No effect was noticed as vortex generators when added separately. The deviation in the drag coefficient from the real car testing was about (6.2%) and shows a very good agreements between the real car test and that of the wind tunnel test.